CLUSTERING OF FOOD SECURITY IN PAPUA ISLAND: WITH AN OPTIMIZED SPATIAL FUZZY CLUSTERING APPROACH - Pasaribu, Rahmat Agung; Astuti, Erni Tri (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Food needs are primary needs that must be met by everyone to maintain their survival. The condition of stable food security is still not evenly distributed throughout Indonesia. Papua Island is one of the regions that has low food security conditions. In identifying the characteristics of food security in Papua Island, it can be done using cluster analysis. The cluster analysis method used in this research is classical FGWC and FGWC with optimization of HHO. This method has considered the spatial element in the grouping process. The purpose of this study is to classify the level of food security in Papua Island and determine the effectiveness of using optimization in FGWC. Based on the evaluation results, it was found that the FGWC-HHO method was the most optimal method with a total of 3 clusters. Cluster 3 consists of 18 regencies is a cluster with a low level of food security, so this cluster can be used as a priority in handling the problem of food security which is still low in Papua Island.